2014
DOI: 10.1007/s10897-014-9762-z
|View full text |Cite
|
Sign up to set email alerts
|

To Reflex or Not: Additional BRCA1/2 Testing in Ashkenazi Jewish Individuals Without Founder Mutations

Abstract: This study determined the prevalence of non-Ashkenazi Jewish BRCA1/2 mutations in the Ashkenazi Jewish population in the state of Michigan, current provider testing practices, and the use of mutation probability models in determining which Ashkenazi Jewish individuals should be offered further analysis following negative BRCA1/2 founder testing. Testing patterns, mutation probabilities, and testing results were assessed for 327 Ashkenazi Jewish individuals seen for BRCA1/2 counseling in the state of Michigan w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A study by Petrucelli et al [13] on the Ashkenazi Jewish population of Michigan found that only 1 out of 166 (0.6%) had a non-founder BRCA1/2 mutation. [13] The authors observed that the National Comprehensive Cancer Network recommends further molecular analysis following a negative founder mutation result only when there is evidence of non-Ashkenazi Jewish ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Petrucelli et al [13] on the Ashkenazi Jewish population of Michigan found that only 1 out of 166 (0.6%) had a non-founder BRCA1/2 mutation. [13] The authors observed that the National Comprehensive Cancer Network recommends further molecular analysis following a negative founder mutation result only when there is evidence of non-Ashkenazi Jewish ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The authors observed that the National Comprehensive Cancer Network recommends further molecular analysis following a negative founder mutation result only when there is evidence of non-Ashkenazi Jewish ancestry. Even though only a small number of counsellees from the current study opted for further analysis when initial founder mutation testing was negative, 40% (4/10) had a non-founder mutation, which is a higher proportion than reflected in Petrucelli et al 's research.…”
Section: Discussionmentioning
confidence: 99%
“…17 Online surveys of cancer genetics providers have demonstrated that providers use various tools to make decisions regarding reflex testing, including family history, risk calculation based on probability models (eg, the BRCAPRO model, 24 the Myriad II model [Myriad Genetics Inc, Salt Lake City, Utah], 25 and the Tyrer-Cuzick model 26 ), the NCCN and US Preventive Services Task Force criteria, institutional criteria, insurance criteria, or review on a case-by-case basis. The literature suggests wide variation in the rates of reflex sequencing among these patients, ranging from 22% to 93%.…”
Section: Discussionmentioning
confidence: 99%
“…17 Online surveys of cancer genetics providers have demonstrated that providers use various tools to make decisions regarding reflex testing, including family history, risk calculation based on probability models (eg, the BRCAPRO model, 24 the Myriad II model [Myriad Genetics Inc, Salt Lake City, Utah], 25 and the Tyrer-Cuzick model 26 ), the NCCN and US Preventive Services Task Force criteria, institutional criteria, insurance criteria, or review on a case-by-case basis. 17 Insurance criteria often play a critical role in decision making because many insurance providers mandate that AJ patients undergo founder mutation testing first and some do not offer coverage for other testing strategies. Although the above mentioned surveys address the use of reflex testing, to the best of our knowledge, patterns of genetic practitioners' use of comprehensive multigene panels in AJ patients as initial screening have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation